2012
DOI: 10.1249/mss.0b013e31824fb8bd
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Locomotor Muscle Fatigue on Joint-Specific Power Production during Cycling

Abstract: Exercise-induced changes in MAXcyc power manifested with differential power loss at each joint action with ankle plantarflexion and knee flexion exhibiting relatively greater fatigue than knee extension and hip extension. However, changes in MAXcyc joint-specific powers were not presaged by changes in TT joint-specific powers. We conclude that fatigue induced via high-intensity cycling does not alter submaximal joint-specific powers but has distinct functional consequences for MAXcyc joint-specific powers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…After the TT, maximum power in the fatigued ipsilateral leg was reduced by 22% and, despite some recovery, remained reduced at 5 min post-TT. These results generally support previous findings (Beelen and Sargeant 1991; Marcora and Staiano 2010a; Elmer et al 2012) of a ~30% reduction in maximum double-leg cycling power and indicate that high-intensity single-leg cycling was effective for inducing fatigue in the ipsilateral leg. The observed exercise-induced reduction in maximum power in the fatigued ipsilateral leg presumably manifested through a combination of central and peripheral mechanisms (Amann 2011), however, additional measurements are needed to confirm this.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After the TT, maximum power in the fatigued ipsilateral leg was reduced by 22% and, despite some recovery, remained reduced at 5 min post-TT. These results generally support previous findings (Beelen and Sargeant 1991; Marcora and Staiano 2010a; Elmer et al 2012) of a ~30% reduction in maximum double-leg cycling power and indicate that high-intensity single-leg cycling was effective for inducing fatigue in the ipsilateral leg. The observed exercise-induced reduction in maximum power in the fatigued ipsilateral leg presumably manifested through a combination of central and peripheral mechanisms (Amann 2011), however, additional measurements are needed to confirm this.…”
Section: Discussionsupporting
confidence: 91%
“…During the TT, participants were able to produce substantial power with one leg (~200 W) which resulted in increases in heart rate, blood lactate, and RPE generally similar to those reported during high-intensity double-leg cycling (Amann et al 2008; Amann et al 2009; Elmer et al 2012; Marcora and Staiano 2010a). Previous authors (Abbiss et al 2011; Bundle et al 2006) have demonstrated that high-intensity single-leg cycling permits higher individual leg power outputs compared to double-leg cycling.…”
Section: Discussionmentioning
confidence: 59%
“…Mean values were calculated over the full pedaling cycle and for both the extension and flexion phase determined from kinematics. The extension phase was defined as an increase in the distance between the pedal and the hip joint, and the flexion phase was defined as a decrease in this distance …”
Section: Methodsmentioning
confidence: 99%
“…The extension phase was defined as an increase in the distance between the pedal and the hip joint, and the flexion phase was defined as a decrease in this distance. 29…”
Section: Motor Coordinationmentioning
confidence: 99%
“…In order to carefully examine whether power output produced at a given sense of effort would be adjusted in response to altered perceptions of peripheral discomfort, the same cycling cadence was used for each 4-s cycling bout in all trials. Using this approach, exercise-induced changes in physiological and perceptual responses along with mechanical output would not be influenced by changes in pedalling rates (Elmer et al, 2012). For each of the five submaximal cycling bouts subjects were instructed to work at a subjective “sense of effort” of 4, 5, 6, 7, and 8 on the modified Borg CR10 “sense of effort scale” (see sense of effort and perceived discomfort scales below), respectively, with 40 s of recovery (15 s of passive rest and 25 s of cycling at ~100 W) interspersing each bout.…”
Section: Methodsmentioning
confidence: 99%